Nutritional and General Awareness of Vitamin D Status among Adult Population in Sulaymaniyah Governorate, Kurdistan Region, Iraq: A Cross-Sectional Study - Mohammed Salih, Reder Rafiq; Shakor, Fadhluddin Nasruddin; Ali, Dalia Ardal; Salih Rashid, Rafiq Mohammed (Kurdistan Journal of Applied Research, 2023)
The health benefits of vitamin D are widely acknowledged by scientific and public health specialists. In Iraq, vitamin D deficiency and inadequacy are highly prevalent. However, public knowledge on this problem is scarce. This research aimed to evaluate the participants’ knowledge about vitamin D, particularly their nutrition-related understanding and behavior, along with their overall attitude toward sun exposure. A descriptive cross-sectional survey of Iraqi adults over 18 was performed with a collection of serum 25(OH)D result between June and September 2022. The observed serum vitamin D indicated that only 25% of the participant had healthy (>30 ng/ml) vitamin D levels. The majority of participants, 90.9%, were aware of vitamin D. Media and primary health care centers were major vitamin D information sources (57.3 and 32%, respectively). Despite believing sunshine is the principal source of vitamin D (90.2%), respondents lacked understanding about the duration (26.3%) and frequency (30%) of sun exposure. In addition, less than 10% of individuals attributed vitamin D shortage to kidney and liver problems, fat malabsorption, obesity, and bariatric surgery. Nevertheless, more than two-thirds (83.3%) of participants defined the positive role of vitamin D in preventing osteoporosis and immune system strengthening (61%). Furthermore, nutritional awareness among the participants was variable. Approximately, 75% misrepresented the percentage of vitamin D supplied by food, over 50% believed that fruit and vegetables are vitamin D sources, 43% of vegetarians are not at risk for vitamin D deficiency, and rather plants considered (70.3%) as an approach to lessen vitamin D deficiency. Additionally, optimal daily intake was recognized by only 10%. Similarly, only 18.3% was aware of the optimal level of serum vitamin D. Notably, 54% was entirely ignorant of the benefits of dietary fortification. Although 55% of the surveyed population used vitamin D supplements, and 76% acknowledged it through their doctor’s recommendation, exceeding two-thirds incorrectly anticipated that drinking tea would impair vitamin D absorption. Therefore, 90% would buy supplements without a prescription if needed. Implementing nutrition education initiatives, encouraging healthy lifestyles, and supporting vitamin D examination should be included in Iraq’s health care system.